2023
DOI: 10.1126/sciadv.adf4487
|View full text |Cite
|
Sign up to set email alerts
|

Artifact geochemistry demonstrates long-distance voyaging in the Polynesian Outliers

Abstract: Although the peopling of Remote Oceania is well-documented as a general process of eastward migrations from Island Southeast Asia and Near Oceania toward the archipelagos of Remote Oceania, the origin and the development of Polynesian societies in the Western Pacific (Polynesian Outliers), far away from the Polynesian triangle, remain unclear. Here, we present a large-scale geochemical sourcing study of stone artifacts excavated from archeological sites in central Vanuatu, the Solomon Islands, and the Caroline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Starting from an initial value of ∼0.699 in chondrites, 17 the 87 Sr/ 86 Sr ratio evolved through time with the radioactive decay of 87 Rb -> 87 Sr ( t 1/2 = 49.61 ± 0.16 Ga) and through geochemical partitioning between Rb, a K-like monovalent alkali metal, and Sr, a Ca-like divalent alkaline-earth metal, resulting in a typical ∼15% variation of the 87 Sr/ 86 Sr value in geological materials. This large range of the 87 Sr/ 86 Sr value has been used for years for different applications, from cosmochemistry, 17,18 mantle and crust geochemistry, 19,20 isotope stratigraphy, 21,22 human and animal past mobility, 23,24 archaeological artifact provenance, 25,26 to forensics 27,28 and goods of value authentication. 29,30…”
Section: Introductionmentioning
confidence: 99%
“…Starting from an initial value of ∼0.699 in chondrites, 17 the 87 Sr/ 86 Sr ratio evolved through time with the radioactive decay of 87 Rb -> 87 Sr ( t 1/2 = 49.61 ± 0.16 Ga) and through geochemical partitioning between Rb, a K-like monovalent alkali metal, and Sr, a Ca-like divalent alkaline-earth metal, resulting in a typical ∼15% variation of the 87 Sr/ 86 Sr value in geological materials. This large range of the 87 Sr/ 86 Sr value has been used for years for different applications, from cosmochemistry, 17,18 mantle and crust geochemistry, 19,20 isotope stratigraphy, 21,22 human and animal past mobility, 23,24 archaeological artifact provenance, 25,26 to forensics 27,28 and goods of value authentication. 29,30…”
Section: Introductionmentioning
confidence: 99%
“…Modern genetic analyses have shown that extant populations from the Polynesian Outliers are not biologically distinct from populations living in the surrounding islands of the Western Pacific, and they do not share more components with Polynesian populations than the populations of the other islands in the region not considered as Polynesian Outliers [3,[31][32][33]. Archaeological research on 12 Polynesian Outliers among the about twenty across Micronesia and Melanesia mentioned in the literature [8] has also not usually revealed archaeological layers containing material typically affiliated with Polynesian culture, although some Polynesian-associated objects such as basalt tools, ornaments, trolling lures and sea mammal teeth pendants have been identified [12,[34][35][36][37][38][39][40]. This situation is unique because linguistic and social features displayed by Polynesian Outlier communities in Vanuatu do not reflect their biological features or material culture.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key lines of evidence for tracing long-distance voyaging and exchange in Oceania has been basalt adzes and associated lithic artefacts (Collerson & Weisler, 2007;Hermann et al, 2023;Jennings et al, 2023;Mills et al, 2008). Basalt adze studies have a long history in Pacific research, ranging from typological and technological (Best, 1977;Clarkson et al, 2014Clarkson et al, , 2015Duff, 1950;Shipton et al, 2016) through to geochemical (Collerson & Weisler, 2007;Kahn et al, 2013;Pengilley et al, 2019;Rolett et al, 2015;Weisler, 1998).…”
Section: Introductionmentioning
confidence: 99%